2019
DOI: 10.1093/jjco/hyz009
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of sunitinib in Japanese patients with progressive, advanced/metastatic, well-differentiated, unresectable pancreatic neuroendocrine tumors: final analyses from a Phase II study

Abstract: This open-label Phase II trial supports the efficacy and safety of sunitinib in Japanese patients with panNETs. Dose reductions and interruptions are critical to maximize the efficacy of sunitinib.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…In fact, panNET patients treated with sunitinib monotherapy reported a longer median PFS that ranged from 12.6 months in a randomized phase III trial including 171 patients to up to 16.8 months in a phase II trial in japanese population [19][20][21]. These studies found a favourable toxicity profile for sunitinib monotherapy and quality of life seem unaffected by this therapeutic approach regardless of diarrhea symptoms [19][20][21][22]. Therefore, sunitinib monotherapy is safer and seems equally or even more effective than the combination of evofosfamide and sunitinib.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, panNET patients treated with sunitinib monotherapy reported a longer median PFS that ranged from 12.6 months in a randomized phase III trial including 171 patients to up to 16.8 months in a phase II trial in japanese population [19][20][21]. These studies found a favourable toxicity profile for sunitinib monotherapy and quality of life seem unaffected by this therapeutic approach regardless of diarrhea symptoms [19][20][21][22]. Therefore, sunitinib monotherapy is safer and seems equally or even more effective than the combination of evofosfamide and sunitinib.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the addition of evofosfamide did not translate into a prolonged PFS with the treatment combination, with a median of 10.4 months. In fact, patients with panNET treated with sunitinib monotherapy reported a longer median PFS, ranging from 12.6 months in a randomized phase III trial including 171 patients to up to 16.8 months in a phase II trial in a Japanese population [19–21]. These studies found a favorable toxicity profile for sunitinib monotherapy, and quality of life seemed unaffected by this therapeutic approach regardless of diarrhea symptoms [19–22].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the authors combined results of phases III and IV of the sunitinib treatment trial, confirming the efficacy of this TKR inhibitor in the tumor ORR (16.7%), and in improving both the median PFS (12.9 months) and the median overall survival (54.1 months) [ 47 ]. Efficacy and safety of sunitinib treatment for this type of pNET were both confirmed in an open-label, phase II trial on 12 Japanese patients [ 48 ]. Unfortunately, data on sunitinib treatment of MEN1 pNETs are still missing.…”
Section: Therapy Of Men1 Pnets: Current Approaches and Future Perspectivesmentioning
confidence: 95%
“…Small molecules that act as inhibiting elements of enzymes reduce their catalytic activity by binding to them. Sunitinib and Sorafenib refer to prototypic instances of small molecule multikinase inhibitors (Ito et al, 2019;Procopio et al, 2019; 1 https://www.cancer.gov/about-cancer/treatment/drugs Verschuur et al, 2019;Zahoor et al, 2019;Mammatas et al, 2020;Ruanglertboon et al, 2020). Consistent with most agents pertaining to the mentioned class, these two drugs suppress PDGFR-α, KIT, VEGFR2, and VEGFR1 in various targets.…”
Section: Enzyme Inhibitormentioning
confidence: 99%